The Effect of Music on Improving the Concentration of Badminton Athletes - Azra Syafira Raihaanun; Sagitarius; Yopi Kusdinar (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
This study aimed to examine the effect of music on improving the concentration of badminton athletes. A quantitative methodology was applied, utilizing a pretest-posttest control group framework. Twelve active badminton club athletes aged 18-22 years were randomly allocated to experimental (n=6) and control (n=6) groups. The experimental group listened to self-selected music for ten minutes before training over a four-week period, whilst the control group sat quietly without music. Concentration was measured using the Concentration Grid Test (CGT) before and after the intervention. Results showed that the experimental group demonstrated a significant increase in concentration scores from pre-test (M=15.50, SD=2.168) to post-test (M=20.00, SD=1.897), while the control group showed minimal change (pre-test: M=11.83, SD=0.753; post-test: M=15.83, SD=0.753). These findings indicate that listening to self-selected music before training measurably enhances badminton athletes' concentration capacity through mechanisms of arousal regulation and attentional focus. Based on these outcomes, it is recommended that a music protocol should be adopted as a cost-effective, easily accessible, and scientifically evidence-based mental preparation strategy, particularly for coaches or institutions with limited access to professional sports psychologists.